The Influence of Consumer Behavior on the Purchase Decision of Bimoli Cooking Oil Products at Kheyla Mart in Baraka District, Enrekang District - Ade Nurfajraini J (Journal AGENCY, 2022)
This study aims to determine behavior on purchasing decisions for Bimoli cooking oil products (case study on Kheyla Mart Baraka). This type of research used in this research is quantitative research. The data collection technique used is a questionnaire or questionnaire by collecting data or information and stating the variables that describe the perception of consumer behavior in purchasing decisions. With a total sample of 95 respondents drawn from the entire population. The results showed that the value of count was 2.730 > table was 1.98525 and a significant value was 0.008 <0.05. Thus H0 is rejected and Ha is accepted, which means that the variable X has a significant positive effect on variable Y. In other words, consumer behavior has a significant positive effect on purchasing decisions.